2014
DOI: 10.5941/myco.2014.42.2.210
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Raffaelea quercus-mongolicae Inoculations on the Formation of Non-conductive Sapwood of Quercus mongolica

Abstract: In Korea, mass mortality of Quercus mongolica trees has become obvious since 2004. Raffaelea quercus-mongolicae is believed to be a causal fungus contributing the mortality. To evaluate the pathogenicity of the fungus to the trees, the fungus was multiple- and single-inoculated to the seedlings and twigs of the mature trees, respectively. In both the inoculations, the fungus was reisolated from more than 50% of inoculated twigs and seedlings. In the single inoculations, proportions of the transverse area of no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…quercus‐mongolicae can colonize sapwood and disrupt sap flow, but pathogenicity of the fungus was not confirmed (Torii et al. ). That recent study might support the exaggerated response hypothesis; however, further inoculation studies are needed to verify the pathogenicity of the fungus.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…quercus‐mongolicae can colonize sapwood and disrupt sap flow, but pathogenicity of the fungus was not confirmed (Torii et al. ). That recent study might support the exaggerated response hypothesis; however, further inoculation studies are needed to verify the pathogenicity of the fungus.…”
Section: Resultsmentioning
confidence: 99%
“…Other possible explanations are that the fungal pathogen could have evolved to overcome resistance of the native hosts or that the fungus is non-pathogenic, but it has the ability to trigger a suicidal overreaction (the exaggerated response hypothesis) of native trees that it contacts (Hulcr and Dunn 2011). A recent study showed that R. quercus-mongolicae can colonize sapwood and disrupt sap flow, but pathogenicity of the fungus was not confirmed (Torii et al 2014). That recent study might support the exaggerated response hypothesis; however, further inoculation studies are needed to verify the pathogenicity of the fungus.…”
Section: Resultsmentioning
confidence: 99%
“…Tree damage and mortality associated with members of the fungal genus Raffaelea have occurred worldwide (Fraedrich et al 2008;In acio et al 2008;Torii et al 2014b). The damage includes mass mortality of fagaceous trees such as Quercus crispula Blume and Quercus serrata Thunb., which has become serious in Japan since the late 1980s .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, R. quercus-mongolicae is considered to be the putative cause of wilt and blight symptoms that subsequently cause tree mortality. Previously, to evaluate the cause of mass mortality of oak trees in South Korea, the virulence of R. quercus-mongolicae on oak trees was assessed; however, these previous pathogenicity tests were inconclusive ( 3 ). Molecular biological investigations on the pathogenicity of R. quercus-mongolicae have not been addressed, largely due to the need for genomic information.…”
Section: Genome Announcementmentioning
confidence: 99%